(untitled) (Colombia Medica, 1986)
The prevalence and distribution of filarial infections among the inhabitants of adjacent regions of the Departamento del Meta, Intendencia del Casanare, and Comisaría del Vichada in northeastern Colombia was determined by collection and examination of blood samples using Knott’s method. Mansonella ozzardi, the only species detected, was found in 2.5% of the samples collected in Meta (6/243), in 4.9% from Casanare (12/247), and 2.5% from Vichada (3/137). All of the microfilaria carriers were Indians who had migrated from other parts of eastern Colombia, principally from the interior of Meta and Vichada. These results indicate that filariasis is not endemic in the regions examined and suggest that an influx of microfilaria carriers with sufficiently high microfilaremia could establish new transmission foci in areas where appropriate vectors are abundant.